Kesatria / Diniey Alleya Adrianna Jeffrie - Jeffrie, Diniey Alleya Adrianna (Universiti Teknologi MARA, Kedah, 2025)
This project proposes o rebranding for Cerito ljop Brunei, a 2D animation founded in 2022 by Aldrin Jalong Baring Anak Melayu in Brunei Darussalam, is a rising star in horror animation. Specializing in engaging horror shorts for the 18+ demographic, particularly young adults, it weaves local folklore with modem storytelling. Primarily hosted on YouTube, the platform captivates audiences with its unique and thrilling narratives, enriching the regional horror genre. Thus, I propose a new direction title Kesatria, Tengku Asmarloka , a revered leader of the Malayan nation, dreams of reforming his divided society. The nation is split into four elemental classes: Sea (elite), Wind (neutral), Fire (wealthy yet marginalized), and Soil (oppressed and impoverished). A colonizer invasion seeking to seize the mystical keris ancient weapons embodying elemental power throws the nation into chaos, deepening social divides and sparking a fierce power struggle. Four warrior.; rise to defend their homeland: Tengku Asmarloka (Sea), Nuluh Tavan (Wind), Lie Yan Zhan (Fire). and Bhumi Pravitha (Soil). However. their differences and prejudices hinder collaboration. They are guided by Adiratna Alina, the stepdaughter of the Permaisuri, a cunning queen who betrays her nation by aiding the colonizers to gain power. Adiratna, opposing her stepmother's corruption, inspires the warriors to embrace unity and mutual respect. Under Tengku Asmarloka's leadership, the warriors confront the colonizers and the Permaisuri's schemes. By overcoming their divisions and working together, they reclaim the keris and restore peace to the nation. Their triumph demonstrates that unity, respect, and courage can conquer even the greatest challenges. leaving a legacy of hope and harmony.